Tourism Empowerment In Society 5.0 Era: Virtual Reality For Covid-19 - Chan, Andi Supriadi; Faza, Sharfina (Publisher: Fakultas Ilmu Komputer, Institution: Universitas Lancang Kuning, 2021)
Medan is the third-largest city in Indonesia, so Medan has various kinds of relics used as tourist attractions. The COVID-19 pandemic has caused a fall in the number of tourist visits and the lack of promotional facilities for potential tourists who will visit. The important circumstances of the conditions that encourage the development of City Tourism Empowerment in the Era of Society 5.0 based on Virtual Reality as one of the researchers' efforts in developing new tourism concepts during a pandemic by using the research method used are the combination method. The survey was conducted by distributing questionnaires to determine the public's perception of VR technology for tourism, especially designing Virtual Reality 3600, using the 6-stage MDCL design model in building VR applications. It was determining the correct hotspot, switching interfaces, and display flow that made it easy. The application results were then tested as VR-based tourism content in Medan city tourism to get a response time value of <1 second and a UAT value of 94% from 20 users from 18-50 years of age.